2018
DOI: 10.1038/s41598-018-29386-7
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic dose response to L-ascorbic acid as an anti-cancer drug in colorectal cancer cell lines according to SVCT-2 expression

Abstract: L-Ascorbic acid (vitamin C, AA) exhibits anti-cancer effects with high-dose treatment through the generation of reactive oxygen species (ROS) and selective damage to cancer cells. The anti-cancer effects of L-ascorbic acid are determined by sodium-dependent vitamin C transporter 2 (SVCT-2), a transporter of L-ascorbic acid. In this study, we demonstrate that L-ascorbic acid treatment showed efficient anti-cancer activity in cell lines with high expression levels of SVCT-2 for a gradient concentration of L-asco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…c-Myc protein expression also increased after treatment with 4.0 pmol cell -1 ascorbate but decreased with 10 pmol cell -1 ascorbate (Figure 1N). These findings are consistent with previous studies which showed oncogenic signals such as Ras and c-myc are involved in the process of hepatocarcinogenesis and regulate the expression of metabolic enzymes which induce cancer cell death by apoptosis 35-37.…”
Section: Resultssupporting
confidence: 93%
“…c-Myc protein expression also increased after treatment with 4.0 pmol cell -1 ascorbate but decreased with 10 pmol cell -1 ascorbate (Figure 1N). These findings are consistent with previous studies which showed oncogenic signals such as Ras and c-myc are involved in the process of hepatocarcinogenesis and regulate the expression of metabolic enzymes which induce cancer cell death by apoptosis 35-37.…”
Section: Resultssupporting
confidence: 93%
“…In the reported experiment, the best antioxidant effect is recorded when the 5% juice solution is administered to HT29 cells. The observed hormetic behavior resembles the response of cancer cell lines to vitamin C and plant flavonoids, which confirms the evidence reported in literature where an excess of exogenous antioxidants can alter the endogenous antioxidant balance and affects, in turn, the defense response [46,47,48]. Thus, only the 1% and 5% juice concentrations (which showed a marked antioxidant effect) have been chosen for further experiments.…”
Section: Resultssupporting
confidence: 85%
“…Therefore, SVCT2 might be implicated in the ascorbate induced cancer cell death phenomena. Similar results were observed by two groups in cholangiocarcinoma cells (Wang et al, 2017), hepatocellular carcinoma (Lv et al, 2018) and colon cancer cells (Cho et al, 2018), where SVCT2 expression determines the susceptibility to pharmacological ascorbate-induced cell death.…”
Section: Vitamin C Transport and Compartmentalization In Cancer Cellssupporting
confidence: 86%